Semantic Roles of The Verb â€œTo Seeâ€ in Javenese of Kertosono - A.A.A Ngr. Adriyanti Weda Ningrat; I Nyoman Kardana; Mirsa Umiyati (RETORIKA: Jurnal Ilmu Bahasa, 2019)
This study reveals the semantic fields from the "to see" verb in Javanese. The aims of this research is to describe the shape, function, meaning and role of semantic of each variant of the verb "to see". To realize this goal, qualitative research design was applied in this study and the semantic role theory of Vole and Van Valin (1984). Was also oriented in data analysis. Verbs that have semantic fields that are associated with the "to see" verb with intentional entities numbering 33. Each of them is ndêlok, ndêlêng, ningali, mirsani, ndeleng sacleraman, ndêlêng tênanên, ningali saestu, mirsani saestu, ningali sekedhap, mirsani sekedhap, mlengos, ngwasi, ngêmatake, ngematakên, ndhangak, dingkluk, nginceng, ngêlirêk, mêntêlêngi, ndelok mburi, and maca. The semantic roles of the arguments of each verb consist of agents and themes. This study only sheds light on the meaning field verb "to see" of the type of variant and a little about the general semantic role. For this reason, a more detailed study of the specific role of each variant of the verb is a topic that can be raised in the next study.